The Main Obstacles to the Development of Digital Economy Infrastructure in Ukraine - Kotelevets Dmytro O. (Bìznes Inform, 2022)
Today, the national economy is developing in the context of active production and use of information and communication technologies. The experience of foreign countries shows that it is impossible to ensure high-quality development of the national economy without the use of such technologies. Digital technologies create new opportunities for economic entities and help to increase their competitiveness. It is also possible to ensure the active development of the digital economy through the introduction of measures to stimulate the development of its infrastructure. However, the outlined system is complex in its structure, and therefore there is a need to identify the basic obstacles that currently hinder the development of the digital economy. This task is accomplished in the article on the basis of a detailed review of international rankings that summarize the basic trends in the digitalization of society based on the analysis of a significant number of indicators. Such rankings include the digital competitiveness rating of countries and the rating based on the network readiness index. A detailed study of the structure of such ratings and the parameters used to establish them has made it possible to find out that the most critical situation in the development of the digital economy infrastructure in Ukraine remains the regulatory and legal framework, which, according to these rankings, is characterized by low quality and imperfection, especially in the field of ICT. The article also specifies that, in general, in international rankings, Ukraine remains holds a rather mediocre position in terms of the development of the digital economy, ranking at 50th place, which is a low indicator, given the potential of our country in the development of digital technologies. Thus, it has been determined that there is an urgent need to develop systematic and realistic directions for the development of the digital economy infrastructure.